Physical Activity, Exercise, and Physiotherapy in Parkinson's Disease: Defining the Concepts - Bouça‐Machado, Raquel (Mov Disord Clin Pract, 2019)
BACKGROUND: Exercise is gaining extreme relevancy as a new therapeutic intervention for Parkinson's disease (PD). However, the frequent misuse of the concepts exercise, physiotherapy, and physical activity limits the possibility of summarizing research findings. This review aims to clarify these concepts and summarize the evidence on exercise in PD. METHODS: We critically appraised physical activity–related concepts and conducted a systematic review of clinical trials evaluating exercise interventions in PD. Additionally, we discussed the implications for PD clinical practice and research. RESULTS: Exercise is a subset of physical activity, and a major component of physiotherapy for PD management, having as the main goal to improve physical fitness. The appraisal of the 83 identified clinical trials found high variability in exercise interventions. Multimodal exercise was the most studied, and 60 minutes, two times/week for 12 weeks, the most reported prescription parameters. CONCLUSION: The best available evidence recommends increasing physical activity levels in PD. Exercise and physiotherapy programs seem the most efficacious strategies to achieve this goal. As a result of the heterogeneity in the type and manner exercise is prescribed, it is not possible to propose strong recommendations for exercise in PD. We believe that, in addition to the clarification of concepts here presented, a collaborative and rigorous work of different areas of knowledge is needed.